2019
DOI: 10.12659/msm.913797
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Decline in Asymptomatic Middle Cerebral Artery Stenosis Patients with Moderate and Poor Collaterals: A 2-Year Follow-Up Study

Abstract: Background The aim of this study was to determine whether poor collaterals contribute to the occurrence of certain types of cognitive disorders in asymptomatic middle cerebral artery stenosis (MCAS). Material/Methods Patients aged ≥45 years with asymptomatic MCAS confirmed by computed tomography angiography were included in a single-center retrospective study. They did not have prior stroke or dementia. Within 7 days of admission, MRI and comprehensive neuropsychologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Recently, a clinical-based study suggested that in participants with asymptomatic severe MCA stenosis, poor collateral circulation was associated with declines in multiple cognitive domains characterised by vascular cognitive impairment. 17 The association between cognitive function and aICAS in other intracranial arteries remains to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a clinical-based study suggested that in participants with asymptomatic severe MCA stenosis, poor collateral circulation was associated with declines in multiple cognitive domains characterised by vascular cognitive impairment. 17 The association between cognitive function and aICAS in other intracranial arteries remains to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Previous study found that patients with poor and moderate collateral circulation in aMCAS had worse cognitive function than patients with good collateral circulation, 13 which suggested that cognitive impairment in patients with aMCAS may be associated with hypoperfusion. This was further confirmed in this study that perfusion decompensation was an independent risk factor for cognitive impairment in patients with aMCAS.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that ICS was a significant risk factor for cognitive decline, independent of the effects of other vascular risk factors and markers of cerebrovascular disease, and may be implicated in the pathophysiology of vascular cognitive impairment. A prospective study investigating the role of cerebral collaterals in patients with middle cerebral artery stenosis showed that patients with ICS but good collaterals did not show an association with cognitive impairment, whereas those with poor collaterals had worse executive function, attention, and information‐processing speed [18]. Previous studies have also shown that patients with ICS and reduced breath‐holding index measured using transcranial Doppler ultrasound had lower cognitive scores [12,32].…”
Section: Discussionmentioning
confidence: 99%
“…Only one prospective study showed that asymptomatic patients with severe middle cerebral artery stenosis and moderate to poor leptomeningeal collaterals had cognitive decline after 2 years [18]. However, this study had a limited sample size ( n = 173), did not use analyses that accounted for repeated measures, and did not take into account other vascular risk factors and markers of cerebrovascular disease.…”
Section: Introductionmentioning
confidence: 99%